Interest spreads and margins in collateral equilibrium with heterogeneous beliefs - Robert B. Barsky; Avery Bogus; Matthew Easton (Federal Reserve Bank of Chicago, 2022)
There continues to be substantial interest in models combining heterogeneous beliefs about asset values with leverage generated by loans from pessimists to the optimistic natural buyers of the asset. This paper determines the size of the interest spread and margin on the loan as a function of the downside risk perceived by the lender, and the amount of risk capital put forward by the borrower. We show that in a continuous state version of a model of collateral equilibrium with high initial leverage, most of the burden of adjustment to increases in such risk are borne by an increase in the interest spread and not the margin or "haircut". This is contrary both to the predictions of the much-discussed binomial asset pricing model and the stylized facts in empirical data from the bilateral repo market.
Keywords: 330